1980
DOI: 10.1007/bf00432369
|View full text |Cite
|
Sign up to set email alerts
|

Chronic administration of haloperidol during development: Behavioral and psychopharmacological effects

Abstract: Chronic haloperidol treatment during prenatal and postnatal development was found to induce long-term behavioral and psychopharmacological effects. Rats tested shortly after termination of the chronic treatment at weaning or as young adults were hyperactive in the open field and exhibited an attenuated behavioral response to amphetamine and an accentuated cataleptic response to later doses of haloperidol, when compared with control offspring of the same age. Tests at an intermediate interval (adolescence perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
1
4

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(55 citation statements)
references
References 21 publications
1
49
1
4
Order By: Relevance
“…Indeed, very little prior research has been done on this topic. We could only find one study that showed a haloperidol-induced sensitization effect on catalepsy (Spear et al, 1980). The lack of research on this topic is not surprising given that antipsychotic sensitization and tolerance are relatively newly recognized phenomena even in adult animals Zhang and Li, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, very little prior research has been done on this topic. We could only find one study that showed a haloperidol-induced sensitization effect on catalepsy (Spear et al, 1980). The lack of research on this topic is not surprising given that antipsychotic sensitization and tolerance are relatively newly recognized phenomena even in adult animals Zhang and Li, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…Ref. [513]). They also frequently appear hyper-reactive to stimuli, displaying substantially greater startle response amplitude than adults (S. Brasser, personal communication).…”
Section: Risk Takingmentioning
confidence: 99%
“…The notion that early experience has prolonged effects on VTA DA functional properties is supported by findings that uncontrollable prenatal stress produced permanent alterations in NAS and prefrontal DA transmission in adulthood (Deminiere et al 1992;Fride & Weinstock 1988). Similarly, persistent changes in DA metabolism and behavior have been observed with the administration of psychostimulants during periods of rapid developmental change (Feigenbaum & Yanai 1984;Middaugh & Zemp 1985;Spear & Brake 1983;Spear et al 1980).…”
Section: Resultsmentioning
confidence: 94%
“…Therefore, the outcomes of such periods might establish different trajectories in the functional development of the VTA DA system across individuals, and thus partially specify eventual trait levels of behavioral facilitation. It is unknown whether experienceexpectant processes are a significant source of individual differences in DA transmission, although the effects of drug-induced DA activation on behavior during periods of rapid developmental change can be persistent (Feigenbaum & Yanai 1984;Middaugh & Zemp 1985;Spear & Brake 1983;Spear et al 1980). An initial task is to identify sensitive periods in the postnatal development of the VTA DA system -for example, as marked behaviorally around 1 year of age in humans by a relatively abrupt increase in locomotor exploration of novel environments.…”
Section: Experience-expectant Processesmentioning
confidence: 99%
See 1 more Smart Citation